A triad of telomerase, androgen receptor and early growth response 1 in prostate cancer cells. Issue 4 (2nd April 2016) - Jacob, Sheeba; Nayak, Sumeet; Kakar, Ruchi; Chaudhari, Uddhav K.; Joshi, Dolly; Vundinti, Babu R.; Fernandes, Gwendolyn; Barai, Ram S.; Kholkute, Sanjeeva D.; Sachdeva, Geetanjali
ABSTRACT: Telomerase activation is one of the key mechanisms that allow cells to bypass replicative senescence. Telomerase activity is primarily regulated at the level of transcription of its catalytic unit- hTERT. Prostate cancer (PCa), akin to other cancers, is characterized by high telomerase activity. Existing data suggest that hTERT expression and telomerase activity are positively regulated by androgenic stimuli in androgen-dependent prostate cancer (ADPC) cells. A part of the present study reaffirmed this by demonstrating a decline in the hTERT expression and telomerase activity on "loss of AR" in ADPC cells. The study further addressed 2 unresolved queries, i) whether AR-mediated signaling is of any relevance to hTERT expression in castration-resistant prostate cancer (CRPC) and ii) whether this signaling involves EGR1. Our data suggest that AR-mediated signaling negatively regulates hTERT expression in CRPC cells. Incidental support for the possibility of EGR1 being a regulator of hTERT expression in PCa was provided by i) immunolocalization of hTERT and EGR1 proteins in the same cell type (secretory epithelium) of PCa and BPH tissues; ii) significantly (p< 0.001) higher levels of both these proteins in CRPC (PC3 and DU145), compared with ADPC (LNCaP) cells. A direct evidence for the role of EGR1 in hTERT expression was evident by a significant (p<0.0001) decrease in the hTERT transcript levels in the EGR1-silenced CRPC cells. Further, "gain of AR" led to a significant reduction in the levels of hTERT and EGR1 in CRPC cells. However, restoration of EGR1 levels prevented the decline in the hTERT transcript levels in these cells. Taken together, our data indicate that AR regulates the expression of EGR1, which in turn acts as a positive regulator of hTERT expression in CRPC cells. Thus, AR exerts an inhibitory effect on hTERT expression and telomerase activity by modulating EGR1 levels in CRPC cells.